Long-Term Potentiation-Like Visual Synaptic Plasticity Is Negatively Associated With Self-Reported Symptoms of Depression and Stress in Healthy Adults - Rygvold, Trine Waage; Hatlestad-Hall, Christoffer; Elvsåshagen, Torbjørn; Moberget, Torgeir; Andersson, Stein (Frontiers in Human Neuroscience, 2022)
Long-term potentiation (LTP) is one of the most extensively studied forms of neuroplasticity and is considered the strongest candidate mechanism for memory and learning. The use of event-related potentials and sensory stimulation paradigms has allowed for the translation from animal studies to non-invasive studies of long-term potentiation (LTP)-like synaptic plasticity in humans. Accumulating evidence suggests that synaptic plasticity as measured by stimulus-specific response modulation is reduced in neuropsychiatric disorders such as major depressive disorder, bipolar disorders and schizophrenia, suggesting that impaired synaptic plasticity plays a part in the underlying pathophysiology of these disorders. This is in line with the neuroplasticity hypothesis of depression, which postulate that deficits in neuroplasticity might be a common pathway underlying depressive disorders. The current study aims to replicate and confirm earlier reports that visual stimulus-specific response modulation is a viable probe into LTP-like synaptic plasticity in a large sample of healthy adults (n = 111). Further, this study explores whether impairments in LTP-like synaptic plasticity is associated with self-reported subclinical depressive symptoms and stress in a healthy population. Consistent with prior research, the current study replicated and confirmed reports demonstrating significant modulation of visual evoked potentials (VEP) following visual high-frequency stimulation. Current results further indicate that reduced LTP-like synaptic plasticity is associated with higher levels of self-reported symptoms of depression and perceived stress. This indicate that LTP-like plasticity is sensitive to sub-clinical levels of psychological distress, and might represent a vulnerability marker for the development of depressive symptoms.